Pengaruh Atribut dan Layanan Terhadap Keputusan Berkunjung dan Kepuasan Wisatawan di Agrowisata Subak Jatiluwih Tabanan: Pengaruh Atribut dan Layanan Terhadap Keputusan Berkunjung dan Kepuasan Wisatawan di Agrowisata Subak Jatiluwih Tabanan - Sherina Agatha Maharani; Ni Made Classia Sukendar (Universitas Duta Bangsa Surakarta, 2025)
Jatiluwih Subak Agrotourism is a leading tourist destination in Bali, renowned for its terraced rice fields and traditional subak irrigation system, which has been recognized by UNESCO as a world cultural heritage site. This study aims to (a) analyze the influence of attributes and services on the decision to visit; (b) analyze the influence of attributes and services on satisfaction; (c) analyze the influence of the decision to visit on satisfaction; (d) analyze the influence of attributes on satisfaction through the decision to visit as a mediating variable; (e) analyze the influence of services on satisfaction through the decision to visit as a mediating variable. This study used qualitative and quantitative approaches, using a survey method using questionnaires distributed to 100 tourist respondents visiting Jatiluwih Subak Agrotourism. Technique analysis used was Structural Equation Modeling with SmartPLS 4.1.1 software. The results showed that (a) attributes significantly influenced the decision to visit; (b) services significantly influenced the decision to visit; (c) attributes significantly influenced satisfaction; (d) services had no significant effect on satisfaction; (e) the decision to visit significantly influenced satisfaction. (f) attributes do not significantly influence satisfaction through the decision to visit as a mediating variable; (g) services significantly influence satisfaction through the decision to visit as a mediating variable. Thus, it is suggested that attribute management and improving service quality are important to increase tourist attractiveness and satisfaction.